2018
DOI: 10.26603/ijspt20180094
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Assessment of Muscular Strength and Balance in Brazilian Elite Futsal Players

Abstract: Purpose/Background: Strength asymmetries are related to knee injuries in intermittent sports players. The purpose of this study was to examine whether elite futsal players demonstrate strength asymmetries during knee isokinetic testing applying the Croisier et al. 21 criteria. Methods:Forty male elite (27.9 ± 6.5 years) Brazilian futsal players participated in the study. The testing protocol required players to perform concentric contractions of both quadriceps and hamstring muscles at angular velocities of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
2
17
1
3
Order By: Relevance
“…Considering torque asymmetries, significant differences were observed between preferred and non-preferred limbs for hamstring concentric contractions at 240°/s and eccentric contractions at 30°/s. Similarly, bilateral asymmetries for soccer and futsal players were observed by other studies as well [ 3 , 4 , 5 , 6 , 31 , 32 ]. Ruas et al [ 31 ] showed that the preferred limb of soccer players presented higher eccentric hamstring strength than the non-preferred limb.…”
Section: Discussionsupporting
confidence: 82%
“…Considering torque asymmetries, significant differences were observed between preferred and non-preferred limbs for hamstring concentric contractions at 240°/s and eccentric contractions at 30°/s. Similarly, bilateral asymmetries for soccer and futsal players were observed by other studies as well [ 3 , 4 , 5 , 6 , 31 , 32 ]. Ruas et al [ 31 ] showed that the preferred limb of soccer players presented higher eccentric hamstring strength than the non-preferred limb.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have presented that stronger and more powerful players of different modalities tend to be faster, have better COD ability, and jump higher (Wilson et al, 1993 ; Newton et al, 2006 ; Freitas et al, 2019 ). In this context, four studies (Cuadrado-Peñafiel et al, 2014 ; Vieira et al, 2016 ; De Lira et al, 2017 ; Nunes et al, 2018 ) investigated the strength capabilities of futsal players ( Table 3 ). Utilizing an isokinetic dynamometer, different authors (Vieira et al, 2016 ; De Lira et al, 2017 ; Nunes et al, 2018 ) assessed elite futsal players' strength levels by reporting peak torque values of the quadriceps and hamstrings.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, four studies (Cuadrado-Peñafiel et al, 2014 ; Vieira et al, 2016 ; De Lira et al, 2017 ; Nunes et al, 2018 ) investigated the strength capabilities of futsal players ( Table 3 ). Utilizing an isokinetic dynamometer, different authors (Vieira et al, 2016 ; De Lira et al, 2017 ; Nunes et al, 2018 ) assessed elite futsal players' strength levels by reporting peak torque values of the quadriceps and hamstrings. De Lira et al ( 2017 ) reported that peak torque values at 60°·s −1 of the dominant leg were 223.9 ± 33.4 N·m for the quadriceps and 128 ± 27.6 N·m for the hamstrings, while the non-dominant leg displayed values of 224 ± 35.8 N·m and 124.1 ± 20.1 N·m −1 for the knee extensors and flexors, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations